An infrared and raman spectroscopic study of transition metal (II) halide quinoline complexes - Yurdakul, S.; Davies, J. Eric D.; AKYÜZ, SEVİM (Elsevier, 1988)
In this study infrared (4000-200 cm−1) and Raman (3500-50 cm−1) spectra are reported for the metal (II) halide quinoline complexes of the following stoichiometries: Mq2Cl2(MMn, Fe, Co, Ni, Cu, Zn or Hg; qquinoline) MqX2 (MCd or Hg; XCl, Br, I); Mq2I2(MCd or Zn) and Mq2Br2(MCo, Ni, Cu or Zn). The MqX2, Hgq2Cl2 and Cdq2I2 complexes have been prepared for the first time. The analysis of the vibrational spectra indicates that there are some structure-spectra correlations.